LOOKING FOR BALANCE. CUSTOMS LAW REVISION COMMISSIONS IN ARGENTINA, 1894-1907. - Rayes, Agustina (Revista de Historia Social y de las Mentalidades, 2021)
In 1894, 1899, and 1907, in Argentina, Customs Laws Review Commissions were formed to carry out studies on the tariff level and the Tarifa de Avalúos (official values applied on export and import taxes). Constituted at the proposal of the Executive Power to inform parliamentary debates on the subject, they were a reflection of the trade policy during the period. Our research is based on customs laws, trade statistics, and discussions and reports of the Review Commissions. We begin with the role of these corps in the dynamics of Argentine tariff policy at the time. Then, we study, on the one hand, their composition and the participation of external actors, and, on the other, the main topics pointed out. Finally, we analyze to what extent the propositions in the subsequent customs laws were considered.